The use of umbrella fish species to provide a more comprehensive approach for freshwater conservation management. Issue 1 (19th November 2021) - Obester, Alyssa N.; Lusardi, Robert A.; Santos, Nicholas R.; Peek, Ryan A.; Yarnell, Sarah M.
Abstract: Where freshwater species populations are in decline, conservation management requires rapid, cost‐effective approaches to develop recommendations, particularly at broad geographical scales or where species‐specific information is lacking. The umbrella species approach, typically applied to terrestrial taxa, is one potentially useful option to inform large‐scale freshwater management efforts. A quantitative, integrated approach is proposed for selecting suites of umbrella fish species over diverse spatial scales using a combination of species ranges, life‐history traits, and species vulnerability scores. The approach also uses expert opinion to validate methods and results. This approach was applied to native fishes in California, and results for two river basins are explored in the context of instream flow management. These examples illustrate how the results could help address two common instream flow management challenges in California: (i) the lack of information related to species‐specific flow requirements in basins with many species; and (ii) the need to move beyond a single species approach to flow management. In addition, the results indicate that the protection of native fishes in California would provide co‐benefits for other aquatic and riparian taxa. A key benefit of this approach is that the data used to select suites of umbrella species (e.g. species ranges, life‐history traits, climate vulnerabilities) are widely available at varying degrees of specificity for most freshwater fishes. Therefore, this flexible approach could be applied in other regions to aid managers in making freshwater conservation decisions, such as for instream flow strategies, in an efficient and cost‐effective manner.